Analysis and comparative description of preparation methods of small cylindrical connections precision surfaces to the assembly - Bratan, Sergey; Bogutsky, Vladimir; Buzko, Alexander; Gutsalenko, Yury (Constantin Brancusi University of Targu Jiu, 2015)
The article describes the methods of finishing precision surfaces of small cylindrical connections.
Keywords: precision surface; confidence limit; wear resistance of surface; finishing; spinning